PENGARUH GAJI DAN INSENTIF TERHADAP KINERJA KARYAWAN PELABUHAN WIRA INDAH PEKANBARU – RIAU - Fatmawati Fatmawati; Gimin Gimin; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of salary and incentives on employee performance at the Port of Wira Indah Pekanbaru Riau. The population in this study were all employees in Wira Indah Port, amounting to 52 people. Samples were obtained using 37 random sampling methods. The analysis data method used is multiple linear regression analysis. Based on the results of the study it is known that employee performance is not good. Bad works is also affected by low salary. Giving salary to employees is categorized as not good, and employee incentives given are considered good. Furthermore, from the results of data analysis, it was found that salary contributions and incentives for employees and workers were 19,3%. This means that to improve the performance of the employees of the company must increase the provision of salaries and incentives that are good or conducive. The higher the salary and incentives, the better the performance. the contrary if the salary and incentives are low then the performance will also be low.Keywords: Salary, Incentives and Employee Performance